The Degree of One Health Implementation in the West Nile Virus Integrated Surveillance in Northern Italy, 2016 - Paternoster, Giulia; Tomassone, Laura; Tamba, Marco; Chiari, Mario; Lavazza, Antonio; Piazzi, Mauro; Favretto, Anna R.; Balduzzi, Giacomo; Pautasso, Alessandra; Vogler, Barbara R. (Frontiers in Public Health, 2017)
West Nile virus (WNV) is endemic in the Po valley area, Northern Italy, and within the legal framework of the national plan for the surveillance of human vector-borne diseases, WNV surveillance has over time been implemented. The surveillance plans are based on the transdisciplinary and trans-sectorial collaboration between regional institutions involved in public, animal, and environmental health. This integrated surveillance targets mosquitoes, wild birds, humans, and horses, and aims at early detecting the viral circulation and reducing the risk of infection in the human populations. The objective of our study was to assess the degree of One Health implementation (One Health-ness) of the WNV surveillance system in three North Italian regions (Emilia-Romagna, Lombardy, Piedmont) in 2016, following the evaluation protocol developed by the Network for Evaluation of One Health (NEOH). In detail, we (i) described the OH initiative (drivers, outcomes) and its system (boundaries, aim, dimensions, actors, stakeholders) and (ii) scored different aspects of this initiative (i.e. OH -thinking, -planning, -sharing, -learning, transdisciplinarity and leadership), with values from zero (= no OH approach) to one (= perfect OH approach). We obtained a mean score for each aspect evaluated. We reached high scores for OH thinking (0.90) and OH planning (0.89). Lower scores were attributed to OH sharing (0.83), transdisciplinarity and leadership (0.77) and OH learning (0.67), highlighting some critical issues related to communication and learning gaps. The strengths and weaknesses detected by the described quantitative evaluation will be investigated in detail by a qualitative evaluation (process evaluation), aiming to provide a basis for the development of shared recommendations to refine the initiative and conduct it in a more One Health oriented perspective.